Revista Comtato: perspectivas atuais da educação especial - Barreto, Rita de Fátima Manhães Gomes (2005)
Comtato Magazine and Current Perspectives of the Special Education - Emphasizing the present description - ideological dimension in our formation, and thinking the challenges of the construction of the knowledge and the reproduction of attitudes concerning the internalization of the difference/deficiency, it points the use of the alternative communication - the Comtato Magazine - as half to express multiple actions and reflections on the special education.